Analisis Mitigasi Resiko Kegagalan Produk Pada Kualitas Pelayanan Menggunakan Metode House of Risk (HOR) - Aldi Rizki; Miranti Putry (Amal Insani Foundation, 2022)
Water is an important factor in human life. The Regional Drinking Water Company (PDAM) is an agency created as part of the government's efforts to meet the community's need for clean water. PDAM Tirta Madani in 2020 will only be able to meet 9.2% of drinking water needs. PDAM's role is to provide drinking water that is clean, healthy and meets health requirements in an area. In order for this role to be realized, action is needed to prevent risks in the company's supply chain from getting worse which results in a decrease in product quality. This study aims to identify risks and risk sources to determine priority risk sources and also propose mitigation designs to reduce the impact of risks. The method used in this study is the Supply Chain Operations Reference (SCOR) to identify risks in the company's business processes and also the House of Risk (HOR) to find priority risk sources and then create appropriate mitigation strategies. The results of the study found 18 risk events with 37 sources of risk. Then obtained 5 priority risk sources with drinking water pipe leaks (A30) in the first position. There are 9 mitigation strategies that can be suggested to reduce the impact of priority risk sources, making a usage schedule (PA7) as the main mitigation strategy.